2019
DOI: 10.1017/s0022029919000037
|View full text |Cite
|
Sign up to set email alerts
|

The impact of organic vs. inorganic selenium on dairy goat productivity and expression of selected genes in milk somatic cells

Abstract: The aim of this study was to determine the effect of diet supplemented with selenized yeast (Se-yeast) on milk yield and milk composition of goats and expression of casein and mammary-gland-immune system genes in milk somatic cells (MSC). Twenty-four dairy goats in their second to fourth lactations were divided into control and experimental groups, balanced according to lactation number and breed (Polish White or Fawn Improved). Morning milk and blood samples were collected four times during lactation (on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…The lack of an effect of Se supplementation on total protein and albumin concentrations in the present study confirms the findings of Shinde et al [21] in calves. However, a study in goats showed that selenium might stimulate protein biosynthesis, and Se supplementation may increase this blood total protein concentration in ruminants, but such effects were observed during much longer studiesafter 160 days of oral supplementation of selenium [31].…”
Section: Discussionmentioning
confidence: 99%
“…The lack of an effect of Se supplementation on total protein and albumin concentrations in the present study confirms the findings of Shinde et al [21] in calves. However, a study in goats showed that selenium might stimulate protein biosynthesis, and Se supplementation may increase this blood total protein concentration in ruminants, but such effects were observed during much longer studiesafter 160 days of oral supplementation of selenium [31].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the use of organic Se in dairy cattle nutrition could be beneficial, especially during transition stress [179] and heat stress [11]. In general, the beneficial effects of using organic Se were demonstrated in a wide variety of species, including chickens [180], turkeys [181], pheasants [182], pigs [8], beef cattle [140,142,149,183,184], sheep [185,186,187], goats [188,189], and horses [190,191].…”
Section: Discussionmentioning
confidence: 99%
“…The feed samples were analyzed for the content of basic components using standard methods [28]. The data on the ingredients and nutrient composition of the basal diet are shown by [29].…”
Section: Animals and Experimental Designmentioning
confidence: 99%